The Effect Of The Marketing Mix On Patient Decision For Treatment At Bhayangkara Hospital Bondowoso - Rini Ekowati; Agustin HP; Muhaimin Dimyati (LPPM Institut Teknologi dan Sains Mandala, 2022)
The purpose of this research is to examine and analyze the effect of the marketing mix on patient decision for treatment to the Bhayangkara Bondowoso Hospital. This research is quantitative descriptive research that use primary data. The research was conducted at Bhayangkara Bondowoso Hospital. Data collection techniques used were observation, interviews, questionnaires, and direct interviews. The number of samples was 175 respondents. The variables used in the Marketing Mix are product, price, promotion, place, people, process, and physical evidence. Data processing is done by using multiple linear regression analysis with the help of the SPSS 25. The results of the research show that the product, price, promotion, place, people, process, and physical evidence simultaneously influence patient decision for treatment. Partially, the product variable has no significant effect on patient decision for treatment. The price variable has no significant effect on patient decision for treatment. The promotion variable has a significant effect on patient decision for treatment. The place quality variable has no significant effect on patient decision for treatment. The process quality variable has a significant effect on the patient decision to seek treatment. The people variable has a significant effect on patient decision for treatment. The physical evidence variable has a significant effect on the patient decision for treatment. The people variable is the most dominant variable in influencing the patient decision for treatment.